Peter Monk and inverse scattering theory. (1st December 2017) - Colton, David
Abstract: Peter Monk has made numerous significant contributions to the field of inverse scattering theory. In the following I try to highlight Peter's most significant achievements in this area with emphasis on the renaissance that took place in the mathematical and numerical treatment of inverse scattering problems that began in the mid 1980s.